An Analytical Review of Deep Learning Models and Datasets for Anomaly-Based Intrusion Detection Systems (Cuestiones de Fisioterapia, 2023)
In the era of increasing cyber threats, anomaly-based intrusion detection systems (IDS) have gained prominence due to their ability to detect previously unknown or evolving attacks. Deep learning has significantly enhanced the accuracy and adaptability of these systems by enabling automatic feature extraction and complex pattern recognition. This review paper has two primary objectives: (1) to study and analyze the existing anomaly-based network intrusion detection systems, and (2) to survey various publicly available datasets and assess their significant features in identifying versatile attack types. For this purpose, a total of 150 research papers were reviewed, out of which 50 were selected based on their relevance, technical novelty, experimental rigor, and alignment with the research objectives. These selected studies encompass state-of-the-art deep learning techniques—including Convolutional Neural Networks (CNNs), Recurrent Neural Networks (RNNs), Long Short-Term Memory (LSTM), Generative Adversarial Networks (GANs), and hybrid models—employed in IDS development. The review also evaluates key benchmark datasets such as NSL-KDD, CICIDS2017, TON_IoT, and CICIDS2017, focusing on their features, applicability, and limitations. Performance metrics, real-time deployment challenges, interpretability, and computational efficiency are discussed in depth. By synthesizing current advancements, gaps, and future research directions, this study provides a comprehensive foundation for designing scalable and intelligent anomaly-based IDS solutions.